Microdeletions of chromosomal region 22q11 in patients with congenital conotruncal cardiac defects. - Goldmuntz, E (J Med Genet, 1993)
Congenital conotruncal cardiac defects occur with increased frequency in patients with DiGeorge syndrome (DGS). Previous studies have shown that the majority of patients with DGS or velocardiofacial syndrome (VCFS) have a microdeletion within chromosomal region 22q11. We hypothesised that patients with conotruncal defects who were not diagnosed with DGS or VCFS would also have 22q11 deletions. Seventeen non-syndromic patients with one of three types of conotruncal defects most commonly seen in DGS or VCFS were evaluated for a 22q11 deletion. DNA probes from within the DiGeorge critical region were used. Heterozygosity at a locus was assessed using restriction fragment length polymorphisms. Copy number was determined by dosage analysis using Southern blot analysis of fluorescence in situ hybridisation of metaphase spreads. Five of 17 patients were shown to have a 22q11 deletion when evaluated by dosage analysis. This study shows a genetic contribution to the development of some conotruncal cardiac malformations and alters knowledge regarding the risk of heritability of these defects in certain cases. IMAGES: